World running down - Hess, Al (Angry Robot, 2023)
"Valentine Weis is a salvager in the future wastelands of Utah. Wrestling with body dysphoria, he dreams of earning enough money to afford citizenship in Salt Lake City--a utopia where the testosterone and surgery he needs to transition is free, the food is plentiful, and folk are much less likely to be shot full of arrows by salt pirates. But earning that kind of money is a pipe dream, until he meets the exceptionally handsome Osric. Once a powerful AI in Salt Lake City, Osric has been forced into an android body against his will and sent into the wasteland to offer Valentine a job on behalf of his new employer--an escort service seeking to retrieve their stolen androids. The reward is a visa into the city, and a chance at the life Valentine's always dreamed of. But as they attempt to recover the "merchandise", they encounter a problem: the android ladies are becoming self-aware, and have no interest in returning to their old lives"--